Evolution of free indirect speech structures in English, American, and Russian literature - A.D. Alimova (Ученые записки Казанского университета: Серия Гуманитарные науки)
Changes that free indirect speech underwent in English, American, and Russian literature during the 20th century were investigated. Both general and more specific (qualitative and quantitative) trends in the free indirect speech development were discussed. Free indirect speech was considered from a diachronic point of view, i.e., the study aims to identify a correlation between the patterns that could be relevant for literary translation from English into Russian and vice versa. Based on the results of the quantitative and qualitative analysis of free indirect speech contexts, it was demonstrated that free indirect speech has evolved. A notable increase in the degree of textual interference and in the variety of models employed was observed. Interestingly, the frequency of occurrence of free indirect speech structures in literary texts varies from decade to decade. Although there are some common trends in free indirect speech usage following the global tendencies in literature, its evolution depends on particular national literary traditions as well. The data obtained show that the most intense usage of free indirect speech segments is typical for the English literature. From the translation perspective, it is important that the general frequency and functional models of indirect speech usage can slightly differ even in texts of the same period or among the writers.